Comparison of the Physical Trace of Global Luminosity Emission at Multiwavelength and Star Formation Rates of Luminous Infrared Galaxies Using Extragalactic Distance Scale Techniques - Shaker, Farah Z.; Al Najm, M.N. (Iraqi Journal of Science, 2024)
This paper aims to study the rate of star formation (SFR) in luminous infrared galaxies at different wavelengths using distance measurement techniques (dl, dm) and to know which methods are the most accurate to determine the rate of star formation as we present through this research the results of the statistical analysis (descriptive statistics) for a sample of luminous infrared galaxies. The data used in this research were collected from the NASA Extragalactic Database (NED) and HYPERLEDA, then used to calculate the star formation rate and indicate the accuracy of the distance methods used (dl, dm). Two methods were tested on Hα, OII, FIR, radio continuum at 1.4 GHz, FUV, NUV, and total (FUV + FIR). The results showed that the dl measurement method has the most accuracy in calculating SFR as it depends on the redshift where the relationship between them is direct. while the other distance method (dm) depends on absolute blue magnitude (MB), it was somewhat less accurate, but the two methods are helpful for this type of calculation.